Experimental Study on the Transition between Static and Kinetic Frictions of Steel/Shale Pairs - Qin Lian; Chunxu Yang; Jifei Cao (Shock and Vibration)
The transition between static and kinetic frictions of steel/shale pairs has been studied. It was found that the coefficient of friction decreased exponentially from static to dynamic friction coefficient with increasing sliding displacement. The difference between static and dynamic friction coefficients and the critical distance Dc under the dry friction condition is much larger than that under the lubricated condition. The transition from static to dynamic friction coefficient is greatly affected by the normal load, quiescent time, and sliding velocity, especially the lubricating condition. Maintaining continuous lubrication of the contact area by the lubricant is crucial to reduce or eliminate the stick-slip motion. The results provide an insight into the transition from static to dynamic friction of steel/shale pairs.